Peaceful Agreements to Share a River - Rene van den Brink; Saish Nevrekar (Tinbergen Institute, 2020)
This paper develops a model of conflict resolution over scarce water in a trans-boundary river. In our model, we consider countries that are located along a river and made a military investment. Given these investments and their location along the river, they sequentially bargain over the surplus of water, or decide to engage in a military conflict with their upstream neighbour. The probability of winning a military conflict is determined by a contest success function which depends on the military investments made before. We speak about a peaceful agreement if the countries rationally decide to bargain over the water instead of engaging into a military conflict. We show that, if all benefit functions are nonnegative, increasing and concave, then for every level of military investment, there always exists a peaceful agreement where every country prefers to bargain peacefully for the water. We provide a scenario that yields one such a peaceful agreement.
Keywords: C78; D62; D74; Q25; 330; River sharing; peaceful agreement; contest success function; subgame perfect equilibrium